2013
DOI: 10.4161/mabs.27435
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization-based antibody cDNA recovery for the production of recombinant antibodies identified by repertoire sequencing

Abstract: (2014) Hybridization-based antibody cDNA recovery for the production of recombinant antibodies identified by repertoire sequencing, mAbs, 6:2, 493-501,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…Fifteen days after immunization, 2 HEL-specific IGHV B cell clones, functionally validated in a previous work, 12 were identified as clones with high relative frequency, but lower Gini coefficients compared to the corresponding high relative frequency clones from control mice, (Fig. 3), suggesting that within the higher frequency range (y axis), antigen-specific clones are the ones having lower Gini coefficient values.…”
Section: Differences In the B Cell Repertoire After An Immune Challengesupporting
confidence: 69%
See 1 more Smart Citation
“…Fifteen days after immunization, 2 HEL-specific IGHV B cell clones, functionally validated in a previous work, 12 were identified as clones with high relative frequency, but lower Gini coefficients compared to the corresponding high relative frequency clones from control mice, (Fig. 3), suggesting that within the higher frequency range (y axis), antigen-specific clones are the ones having lower Gini coefficient values.…”
Section: Differences In the B Cell Repertoire After An Immune Challengesupporting
confidence: 69%
“…31 As a proof of principle of ImmunediveRsity performance to digitally reconstruct the antibody repertoire with experimental data, we used our previously described IGHV sequence data derived from libraries (IgM and IgG class) from 2 BALB/c mice spleens at 3, 7 and 15 days postimmunization with hen egg lysozyme (HEL) and one mouse inoculated with PBS in each time point as controls. 12 The sequencing metrics of the 18 sequenced libraries are shown on Table S1. As expected, the proportion of somatic hypermutation was higher in the IgG than in the IgM compartment (Fig.…”
Section: Differences In the B Cell Repertoire After An Immune Challengementioning
confidence: 99%
“…The two biggest lineages of the largest heavy chain clonotypes of clonal expansions observed in silico were selected for experimental validation of anti-Influenza virus specificity. The sequence corresponding to the V H region flanked by EcoR I and Nhe I restriction sites were synthesized as gene fragments (Gblocks, IDT) and cloned in the expression vector of human antibody heavy chains pVAJO-CHG1, plasmid coding for human IgG1, as described [ 38 ]. The selected V H sequences were matched with seven different variable region sequences of light chain (VL) (See Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we suggest the NGS technique based on the antibody transcriptome as an efficient and universal method to deal with various intricate cases, since it can clarify all of the VR gene sequence diversities and gene abundances of individual hybridomas, complemented with specific PCR to amplify exact full-length sequences of the VH and VL. Normally, the clones with the highest amplification frequency are considered to be antigen-specific, i.e., the highly amplified VH and VL genes were paired to construct the rAbs, however subsequent experiments confirmed that the majority of clones were actually antigen-specific [ 42 , 43 ]. However, Bradbury et al hold the opposite viewpoint that the most abundant transcripts of VH and VL found in a hybridoma do not exactly translate to the antibody displaying the desired sensitivity and specificity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%